2020
DOI: 10.1007/s00428-020-02779-8
|View full text |Cite
|
Sign up to set email alerts
|

Autopsy in adults with congenital heart disease (ACHD)

Abstract: The adult congenital heart diseases (ACHD) population is exceeding the pediatric congenital heart diseases (CHD) population and is progressively expanding each year, representing more than 90% of patients with CHD. Of these, about 75% have undergone surgical and/or percutaneous intervention for palliation or correction. Autopsy can be a very challenging procedure in ACHD patients. The approach and protocol to be used may vary depending on whether the pathologists are facing native disease without surgical or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Prior medication information was obtained based on the description provided in the autopsy and toxicology report. The final cause of death was ascertained based on the data present in the autopsy report (after toxicological and the anatomopathological diagnosis), in the light of the Guidelines for autopsy investigation of sudden cardiac death (2017) 5 , 14 . Finally, deaths in which both autopsy and toxicology investigations were inconclusive, non-cardiac etiologies were excluded, and the heart had non-diagnostic pathological findings of uncertain significance at gross and histological examination, 15 were classified as possible SADS as the final cause of death 4 .…”
Section: Methodsmentioning
confidence: 99%
“…Prior medication information was obtained based on the description provided in the autopsy and toxicology report. The final cause of death was ascertained based on the data present in the autopsy report (after toxicological and the anatomopathological diagnosis), in the light of the Guidelines for autopsy investigation of sudden cardiac death (2017) 5 , 14 . Finally, deaths in which both autopsy and toxicology investigations were inconclusive, non-cardiac etiologies were excluded, and the heart had non-diagnostic pathological findings of uncertain significance at gross and histological examination, 15 were classified as possible SADS as the final cause of death 4 .…”
Section: Methodsmentioning
confidence: 99%
“…A complete autopsy was performed according to the standard protocol adopted in our centre and previously published both for post-transplant [ 5 ] or adult CHD [ 6 ] cases. Histopathology was part of the complete autopsy, and the liver samples were collected and stained with Haematoxylin–Eosin and Masson’s Trichromic (Diapath S.p.A., Martinengo (BG), Italy) for evaluation both of the extracellular matrix and fibrous pattern.…”
Section: Methodsmentioning
confidence: 99%
“…Recent guidelines from the European Association of Cardiovascular Pathology describe the most common types of CHDs and include a description of the various types of surgical and percutaneous procedures and major pathological complications. This is a valuable guide to pathologists facing such an autopsy [ 17 ]. Small autopsy studies in the forensic area relate to SCD cases with known CHD in the majority but this study also showed that five cases had no diagnosis prior to autopsy, highlighting that the first presentation of CHD can be SCD like in the Danish study [ 15 ].…”
Section: Value Of the Autopsy In Chdmentioning
confidence: 99%